POPULARITAS SINDHEN - Jazuli, M (Harmonia: Journal of Arts Research and Education, 2009)
Apparently, the sindhÃÂ¨n life, today, have not been far from celebrities one or otherarties with many other styles and beautiful tricked performances. Therefore, it isnatural, that every sindhÃÂ¨n always wants to be popular, famous, and amazed bymany people with the result that they can do the ways to reach what they wantto. But, how to be a sindhÃÂ¨n, what trick to get to become a popular sindhÃÂ¨n, andhow to hold their existence so that they constantly get interest of wide society.The questions above will be answered in this article which is a research result ofpopular sindhÃÂ¨n in Semarang by using quantitative paradigm. First, the ways tobe a sindhÃÂ¨n has four factors, namely the way to learn, its surrounding, socialassociate, and laku brata. Second, the sindhÃÂ¨n popularity is appeared from theirhigh stage-performance (20 to 25 times per month), the stage area reach out ofprovince, quality of artistic trough their special style, having wide influentialsponsor, and getting compensation between four to five millions each their stage.Third, the ways of sindhÃÂ¨n to maintain their attractive power for society attentionare taken on such as : (1) maintaining pattern and increasing quality and itscharacteristic, namely trough the colour of their soft voices, making gregel andwiledan so that their voices always impress such as tregel, rongÃÂªh, renyah, and berakfor the listeners; (2) they must be self confidence in pesindhÃÂªnan, there is no otherjob except the sindhÃÂ¨n , such as langgam, campursari, and keroncong dangdut; (3)they must plait together social relation to the people who have wide influence aswell as art organisations; (4) they always surrender to the god trough laku brataas their belief.Key word: sindhÃÂ©n, popularitas